2003
DOI: 10.1177/154405910308200817
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Brain Regional Activity during Chewing: A Functional Magnetic Resonance Imaging Study

Abstract: Age-related changes in mastication-induced brain neuronal activity have been suggested. However, in humans, little is known about the anatomical regions involved. Using fMRI during cycles of rhythmic gum-chewing and no chewing, we have examined the effect of aging on brain regional activity during chewing in young adult (19-26 yrs), middle-aged (42-55 yrs), and aged (65-73 yrs) healthy humans. In all subjects, chewing resulted in a bilateral increase in the BOLD signals in the sensorimotor cortex, cerebellum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
2
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 20 publications
11
131
2
3
Order By: Relevance
“…A systematic literature search identified 10 studies that directly compared movement-related BOLD responses between younger and older participants. Nine of these studies studied 13 or less individuals per group (Fang et al, 2005;Heuninckx et al, 2005Heuninckx et al, , 2008aHutchinson et al, 2002;Mattay et al, 2002;Onozuka et al, 2003;Riecker et al, 2006;Taniwaki et al, 2007;Wu and Hallett, 2005). Only one study investigated more than 13 individuals in one group (12 younger vs. 26 older adults) (Heuninckx et al, 2008b).…”
Section: Sample Size and Statistical Powermentioning
confidence: 99%
“…A systematic literature search identified 10 studies that directly compared movement-related BOLD responses between younger and older participants. Nine of these studies studied 13 or less individuals per group (Fang et al, 2005;Heuninckx et al, 2005Heuninckx et al, , 2008aHutchinson et al, 2002;Mattay et al, 2002;Onozuka et al, 2003;Riecker et al, 2006;Taniwaki et al, 2007;Wu and Hallett, 2005). Only one study investigated more than 13 individuals in one group (12 younger vs. 26 older adults) (Heuninckx et al, 2008b).…”
Section: Sample Size and Statistical Powermentioning
confidence: 99%
“…Chewing resulted in a bilateral increase in blood oxygenation level-dependent (BOLD) signals in the sensorimotor cortex, cerebellum, thalamus, supplementary motor area, and insula, and a unilateral increase in the right prefrontal area. Interestingly, the increase in the right prefrontal area was remarkable in aged subjects and up to 4 times higher than that seen in young subjects (Onozuka et al, 2003). Grady et al (2001) showed that increased right prefrontal cortex activity is associated with better memory performance.…”
Section: Brain Activitymentioning
confidence: 97%
“…Previous fMRI studies on gum chewing focused on the percentage of changes in fMRI signals, [1][2][3][4] although the pixel counts were not measured across slices. The present study showed an increase in the spatial extent of fMRI signals in the primary sensorimotor cortex with an increasing magnitude of bite force.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Brain activation associated with gum chewing results in an increase in fMRI signals; however, the factors that influence motor cortex activity have not been fully elucidated. Chewing is a complicated movement that involves opening and closing of the mouth and includes several parameters, such as the force, direction, and speed of chewing.…”
Section: Introductionmentioning
confidence: 99%